Genome-Wide Analysis of Left Ventricular Maximum Wall Thickness in the UK Biobank Cohort Reveals a Shared Genetic Background With Hypertrophic Cardiomyopathy. (4th January 2023) - Aung, Nay; Lopes, Luis R.; van Duijvenboden, Stefan; Harper, Andrew R.; Goel, Anuj; Grace, Christopher; Ho, Carolyn Y.; Weintraub, William S.; Kramer, Christopher M.; Neubauer, Stefan; Watkins, Hugh C.; Petersen, Steffen E.; et al.
Abstract : Background: Left ventricular maximum wall thickness (LVMWT) is an important biomarker of left ventricular hypertrophy and provides diagnostic and prognostic information in hypertrophic cardiomyopathy (HCM). Limited information is available on the genetic determinants of LVMWT. Methods: We performed a genome-wide association study of LVMWT measured from the cardiovascular magnetic resonance examinations of 42 176 European individuals. We evaluated the genetic relationship between LVMWT and HCM by performing pairwise analysis using the data from the Hypertrophic Cardiomyopathy Registry in which the controls were randomly selected from UK Biobank individuals not included in the cardiovascular magnetic resonance sub-study. Results: Twenty-one genetic loci were discovered at P <5×10 −8 . Several novel candidate genes were identified including PROX1, PXN, and PTK2, with known functional roles in myocardial growth and sarcomere organization. The LVMWT genetic risk score is predictive of HCM in the Hypertrophic Cardiomyopathy Registry (odds ratio per SD: 1.18 [95% CI, 1.13–1.23]) with pairwise analyses demonstrating a moderate genetic correlation (rg =0.53) and substantial loci overlap (19/21). Conclusions: Our findings provide novel insights into the genetic underpinning of LVMWT and highlight its shared genetic background with HCM, supporting future endeavours to elucidate the genetic etiology of HCM.